Pengaruh Kualitas Layanan Terhadap Citra Merek, Kepuasan Dan Kepercayaan Konsumen Lembaga Pendidikan Kursus Dan Pelatihan Pasca SMA Di Jawa Tengah - Fatonah, Siti (-)
Every educational institution conducts a number of efforts to satisfy its consumers, including Course and training institutions. it is not  easy to Implement consumers'satisfaction, moreover, recently tile quantity Of Course takers are higher than several years ago- It can be recognized by the limited domestic job opportunity that causes unbalanced  between the work-force increasing and tile domestic job necessity. This matter significantly leads to the increasing of unemployment In this case of the unemployment, the Course institutions  keep their existence by improving the program quality demand in relation of service quality implemented to the consumer oriented service fonn.  It happens to a large number of the Course and training institutions In Center Java, therefore they always make efforts to improve the service quality in purpose of Improving institution image By the improvement The institutions would implement the Consumer satisfaction and trust.By tile use Of Generalized Least Square (GLS) and Structural Model (SEM) that nm through AMOS 6.l' software to 300 respondents, the research explains the influence of set-vice quality  toward  brand  image consumer  satisfaction  and  trust among  the Course and training institution  In East Java.In this research, the value of the first Determination  Coefficient (R2) is 0,651. It shows that maximum service quality can increase the image of tile course and training institutions In East Java by 65.1 %. The value of the second Determination Coefficient (R2) is 0,592. It shows that with maximum set-vice quality and brand image can raise satisfaction among tile: training and course  takers in East Java by 59.2%. And the third Determination Coefficient value (R2) is 0,688. It show; that with the maximum service quality, brand image and Consumers'  satisfaction can increase the trust of the training and course takers in East Java by 68.8%.Keywords:  Training and Course Institutions in East Java, Service Quality, Brand Image, Consumer Satisfaction, Consumer Trust.